Dynamics of magnetic Janus colloids studied by ultra small-angle X-ray photon correlation spectroscopy. Issue 13 (23rd November 2022) - Zinn, Thomas; Sharpnack, Lewis; Narayanan, Theyencheri
Abstract : Advanced synchrotron scattering methods elucidate the chain-like ordering and associated dynamics of magnetic Janus particles as a function of magnetic field. Particle dynamics slows down anisotropically with the magnetic field. Abstract : The orientation behavior and the translational dynamics of spherical magnetic silica-nickel Janus colloids in an external magnetic field have been studied by small-angle X-ray scattering and X-ray photon correlation spectroscopy at ultra small-angles. For weak applied fields and at low volume fractions, the particle dynamics is dominated by Brownian motion even though the net magnetic moments of the individual particles are aligned in the direction of the field as indicated by the anisotropy in the small-angle scattering patterns. For higher fields the magnetic forces result in more complex structural changes with nickel caps of Janus particles pointing predominantly along the applied magnetic field. The alignment ultimately leads to chain-like configurations and the intensity–intensity autocorrelation functions, g 2 ( q, t ), show a second slower decay which becomes more pronounced at higher volume fractions. A direction dependent analysis of g 2 ( q, t ) revealed a faster than exponential decay perpendicular to the field which is related to the sedimentation of magnetically ordered domains. The corresponding velocity fluctuations could be decoupled from the diffusion of particles by decomposing g 2 ( q, t ) into advective and diffusive contributions. Finally, the particle dynamics becomes anisotropic at higher volume fractions and strong magnetic fields. The derived translational diffusion coefficients indicate slower particle dynamics perpendicular to the field as compared to the parallel direction.